Improving employee Innovation Behavior for better future in Electrical Industry - Aryana Satrya; Ilham Kamal (Green Publisher Indonesia, 2024)
This study aimed to investigate and assess the effect of Proactive Personality (PP), Work Motivation (WM), Perceive Organizational Support (POS) on Innovative Work Behavior (IWB), with Work Engagement.acting as mediators. Questionnaires were used in this quantitative study, to obtain information from 300 employees, with subsequent analysis implementing the Structural Equation Model Lisrel 8.3. The results showed that IWB was significantly influenced by WM, POS,PP, WE. The results also showed WM, POS, PP significantly influenced WE. Moreover, WM, POS,PP significantly influenced IWB mediated by WE. This study investigated innovative work behavior that significantly and widely impacted by Perceive Organizational Support. It also provided a deeper comprehension of the employee characteristic in the industry like work motivaton, proactive personality, work engagement.